Protecting The Marine Environment of The Gaza Strip Under The Provisions of International Humanitarian Law - Abuhasballah, Belal Ali (International Journal of Global Community, 2023)
The purpose of this study is to examine the role of international humanitarian law in protecting the marine environment of the Gaza Strip in light of the Israeli violations, as well as to clarify the effectiveness of the rules of international humanitarian law in protecting the marine environment of Palestine in light of the violations of the Israeli occupation. The mere conclusion of international treaties to protect the marine environment is not enough without a supreme authority imposing penalties on violators. On the other hand, the Israeli occupation violates on a daily basis the rules of international humanitarian law that provide protection for the marine environment of Palestine without deterrence from the international community. Therefore, the study recommends the need for the international community and international organizations to take all necessary measures to deter Israel, oblige it to the provisions of international law, stop its violations against the marine environment and carry out its duties as an occupying military force.